Exploring balanced harvesting by using an Atlantis ecosystem model for the Nordic and Barents Seas - Nilsen, Ina (The University of Bergen, 2018)
To meet the objectives of the Ecosystem Approach to Fisheries, “Balanced Harvesting” (BH) has been suggested as a possible strategy to ensure a high sustainable yield while maintaining ecosystem structure and function. BH proposes a moderate fishing mortality in proportion to productivity spread across the widest possible range of species, stocks, and sizes in an ecosystem. The intent is a sustainable and overall unselective harvest that reduces alterations to the ecosystem structure by maintaining the relative size and species composition, while increasing total yield. The Norwegian and Barents Seas have been subjected to moderate fishing pressure and elements of an ecosystem-based approach to management for many years. By using a pre-parameterized Atlantis ecosystem model of the Nordic and Barents Seas, we investigated the ecosystem effects of a BH regime. This was done by running simulations with combinations of historic fishing pressure and fishing mortality rates proportional to 25% of the productivity of selected species. The simulations were then compared to a control run where the historical fisheries were applied. The model results imply that implementing a BH regime in the Norwegian and Barents Seas would only produce marginal increases in total yields of commercially exploited stocks, possibly because the Norwegian fisheries already is fairly balanced. The inclusion of non-commercial species in the harvest, on both lower and higher trophic levels, caused unexpectedly drastic changes to the ecosystem in the form of stock collapses or severely changed biomass levels. This study represents the first attempted examination of implementing balanced harvesting based on productivity, using an Atlantis ecosystem model. Masteroppgave i biologi MAMN-BIO BIO399